Developing an Integrated Digital Marketing Strategy to Increase Purchase Intention Based on Customer Preferences Toward Marketing Mix and Social Media Content: a Case Study of Graduats Online Upskilling Platform - Lavena Laduri; Neneng Nurlaela Arief (Publikasi Indonesia, 2026)
Increased activity in Indonesia’s online learning market has forced companies to compete more fiercely for the attention of recent graduates and young workers. However, many emerging platforms still face challenges in building brand visibility, credibility, and conversion effectiveness, despite the extensive use of social media for information search and learning evaluation. This study aims to develop an integrated digital marketing strategy for Graduats by analyzing customer preferences toward Social Media Marketing Activities (SMMAs) and relevant elements of the 7P service marketing mix, as well as how these factors influence purchase intention. A survey-based quantitative method was utilized, focusing on individuals between 18 and 30 years old to align with the primary demographic of Graduates. The findings reveal that social media content significantly influences purchase intention, particularly when it communicates credibility, perceived learning value, and user engagement. Instagram is identified as the most dominant platform for both social interaction and upskilling-related information search. Moreover, the combined influence of entertainment, interactivity, trendiness, and e-WOM explains 81.3% of the variance in purchase intention, emphasizing the strong role of content-driven strategies. Based on these results, this study proposes an integrated digital marketing framework comprising an SMMA-based content strategy and an implementation design using the RACE model. This research provides managerial implications for optimizing social media marketing investments and contributes academically by extending the application of SMMA to Indonesia’s online upskilling sector.